Pengembangan Media Pembelajaran Monopoli Pada Mata Pelajaran Pendidikan Pancasila Sebagai Upaya Pencegahan Bullying Peserta Didik Kelas V SDN Kepatihan 03 Jember - Sefvira Ayu Primadani (Fakultas Keguruan Dan Ilmu Pendidikan Pendidikan Guru Sekolah Dasar, 2025)
The problem in this study is the occurrence of bullying behavior and students do not understand the material, especially in the Pancasila Education subject because the media taught is still conventional. This makes students easily feel bored and more fun joking with their deskmates, so that learning innovation is needed. The purpose of this study is to develop and determine the validity, effectiveness, and practicality of monopoly learning media in the Pancasila Education subject as an effort to prevent bullying. This type of research is a development research (Research and Development) by Bogn and Gall which consists of 10 stages, but in this study only up to stage 8 because it can answer the problem formulation. Data analysis techniques used are validity analysis, effectiveness analysis, and practicality analysis. The results of the validation of the developed product obtained a score of 86.6% with a very feasible category. The effectiveness test with a learning outcome test obtained a score of 82.6% with a very effective category. The practicality test through a student response questionnaire obtained a score of 91.7% with a very practical category. Based on this description, it can be concluded that the Monopoly learning media meets the requirements of validity, effectiveness, and practicality, making it suitable for use in the learning process of Pancasila Education for fifth grade at SDN Kepatihan 03 Jember.
Keywords: Monopoly Media; Pancasila Education; Bullying Prevention